A Method to Extract the Structural Strata and Elements of Landscape Using GIS - Kazunari Tanaka; Nami Tanaka (European Regional Science Association (ERSA), 2006)
Analyzing the landscape with using large three-dimensional database is well noted as the new method. In applying the method, the measure to divide the database into several densities of data to adjust many places and to analyze in mainframe computer is in need. The purpose of this study is to clarify the method of dividing spaces into structural layer, which can be measured in its quantity._ The theoretical method to extract the landscape elements by the distance from the viewpoint has been recognized by the previous studies, which based on the human phenomenon philosophy. However, the quantities of distance, which defines the space as a whole environment around viewpoint is not yet applicable for practical design. Because, the quantities have not been clearly found to apply to the real space since, feelings of distance varies by personal image. The cause of differences are due to some factors such as physical factors including the topography, the vegetation, and the building surroundings. Furthermore, there are other factors for example, psychological and social._ In this study, the physically caused distance definition is to be cleared through the method to extract the structural strata and the elements of landscape._ As an initial analysis, the angle of gaze from viewpoint, based on human engineering, the heights of the layers were examined and clearly found. The relationship between the eyesight and the angle of gaze are analyzed. Secondly, the continuity of figure from viewpoint are measured. It applied the fifty meters mesh digital map, the topographic vector data, the aerial photograph, and the building form vector data, to the Geographic Information System; the SIS and the ArcGIS. It proved that three scale of view; the close, the distance, and the background divides the real landscape. With this result, the method to extract the structural strata are found._ Preliminary, the methods\~O application was tried to real spaces for further analysis. The results encouraged the analysis of physical quantity related with the human image including the time-space, and the relationship between the view and the other sense, which are under processes._
Keywords: 330